2008
DOI: 10.1007/s12560-008-9002-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Norovirus Genogroups I and II in Environmental and Clinical Samples Using TaqMan Real-Time RT-PCR

Abstract: Noroviruses (NoVs) are a major cause of acute non-bacterial gastroenteritis in all age groups. They efficiently circulate in both clinical and environmental contexts. In this study, real-time RT-PCR methods based on TaqMan probe technology were used to enumerate human noroviruses (genogroups I and II) in clinical samples, and in estuarine, seawater and sewage water samples, with the aim of obtaining quantitative information on the level of viral contamination. This was achieved through a quantitative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…Similar to previous studies that reported high viral loads in patients with NoV gastroenteritis [31,32], a high viral load was detected in both of the patients with a GIV NoV infection. Based on these findings, it is suggested that a NoV GIV.1 infection can cause severe diarrhea in children under 5 years of age.…”
Section: Similar and Contrasting Cases In The Literature And Discussionsupporting
confidence: 89%
“…Similar to previous studies that reported high viral loads in patients with NoV gastroenteritis [31,32], a high viral load was detected in both of the patients with a GIV NoV infection. Based on these findings, it is suggested that a NoV GIV.1 infection can cause severe diarrhea in children under 5 years of age.…”
Section: Similar and Contrasting Cases In The Literature And Discussionsupporting
confidence: 89%
“…Even when used as a secondary step, ultracentrifugation has been shown to concentrate inhibitors (Casas et al 2007). Successful protocols have been developed using ultracentrifugation on highly purified preparations (La Rosa et al 2009). In addition, ultracentrifugation has the disadvantage of requiring expensive and highly specialized equipment.…”
Section: Sample Preparationmentioning
confidence: 99%
“…A first factor is the low presumed 50% infectious dose (ID 50 ) of 18 segregated infectious NoV particles (Teunis et al, 2008). Other factors include the shedding of high amounts of virus particles (up to 10 10 virus particles per gram feces) (Jeong et al, 2013;Lai et al, 2012;La Rosa et al, 2009;Atmar et al, 2008;Ozawa et al, 2007;Lee et al, 2007;Chan et al, 2006), a high environmental stability Wang et al, 2013;Baert et al, 2009a) and the frequent occurrence of asymptomatic infections (Jeong et al, 2013;Nicolay et al, 2011;Phillips et al, 2010). Regarding HuNoV post-harvest contamination of foods, a recent study found that in 42.5% of described HuNoV food borne outbreaks between 2000 and 2008 an infected food handler was responsible (Baert et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%